Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1103/physrevb.28.2317
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of actinide elements having the5f6and5f7electronic

Abstract: Magnetic susceptibility measurements have been made on multimicrogram quantities of AmF3, '4'CmF4, "'CmO2, and ' 'CmBa03 samples (nominally the 5f electronic configuration) and on ' 'CmzO&, '"'CmF3, ' BkF"and ' BkOz (nominally the 5f' electronic configuration) in the temperature range 4.2 -300 K and in magnetic fields up to 1650 G. The experimentally determined effective magnetic moments and the Curie-gneiss constants for these compounds are presented. The deviation of the moments for the 5f compounds from tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…Examining Fig. 18(a), (b), and (c) together clearly shows that if the intermediate coupling curve remained near the jj limit for Cm, the spin (and total) magnetic moment would be much smaller than the observed ~8 μ B /atom magnetic moment (Marei and Cunningham, 1972;Huray et al, 1980;Nave et al, 1983;Huray and Nave, 1987) and have little or no effect on the crystal structure of the metal.…”
Section: G Curiummentioning
confidence: 99%
See 1 more Smart Citation
“…Examining Fig. 18(a), (b), and (c) together clearly shows that if the intermediate coupling curve remained near the jj limit for Cm, the spin (and total) magnetic moment would be much smaller than the observed ~8 μ B /atom magnetic moment (Marei and Cunningham, 1972;Huray et al, 1980;Nave et al, 1983;Huray and Nave, 1987) and have little or no effect on the crystal structure of the metal.…”
Section: G Curiummentioning
confidence: 99%
“…This creates a strong spin polarization though Hund's rule, producing an effective magnetic moment of ~8 μ B /atom in Cm metal (Marei and Cunningham, 1972;Huray et al, 1980;Nave et al, 1983;Huray and Nave, 1987). Pu, Am, and Cm all exhibit intermediate coupling; however, while Pu and Am exhibit strong spin-orbit interactions, Cm is strongly shifted towards the LS limit.…”
Section: G Curiummentioning
confidence: 99%
“…[60] It has been shown that, for a range of off-stoichiometric compounds CmO 2−x , both the lattice parameter and magnetic moment increase with x. [61,62,63] Given the expected moments of Cm 3+ (5f 7 ; µ ef f =7.94 µ B ) and Cm 4+ (5f 6 ; µ ef f =0 µ B ) it was noted that this trend indicates an increase in the number of Cm 3+ impurities as we move away from stoichiometry. Based on the ionic picture, one accordingly expects the Cm 4+ ground state configuration for the stoichiometric compound, which however seems to be contradicted by the fact that in samples very close to stoichimetry, [64] susceptibility measurements give the effective moment as high as µ ef f = 3.36 µ B .…”
Section: Sic-lsd Electronic Structurementioning
confidence: 99%
“…Although the perovskites BaMOa are significantly more stable than the binary oxides (43), the perovskite BaCmO3 still showed significant Cm(III) from magnetic measurements (27). Quantitative results on the enthalpy of stabilization of numerous uranium, neptunium, and most recently plutoniura complex oxides should guide efforts to synthesize new complex oxides of Am and Cm (44,45).…”
Section: Complex Oxides Of Americium and Curiummentioning
confidence: 99%
“…Despite the more recent availability of 2 **^Cm, which appeared from thermogravimetric measurements and X-ray powder diffraction lattice parameter to yield stoichiometric CmO2.00 in oxygen at 1 atm pressure, recent magnetic susceptibility determinations infer significant hypostoichiometry (x near 0.2 in CmO 2 _ ) (24)(25)(26)(27). Very careful annealing in pure oxygen for several days at 1 atm pressure and even at 100 atm pressure (25,26) failed to eliminate Curie-Weiss paramagnetism attributable to Cra(III).…”
Section: Curium Oxidesmentioning
confidence: 99%